1986
DOI: 10.1017/s0143385700003254
|View full text |Cite
|
Sign up to set email alerts
|

Transitivity and the centre for maps of the circle

Abstract: Abstract. We study the dynamics of continuous maps of the circle with periodic points. We show that the centre is the closure of the periodic points and that the depth of the centre is at most two. We also characterize the property that every power is transitive in terms of transitivity of a single power and some periodic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Coven and Mulvey in [23] extended Theorem 1.1 to the circle proving that for transitive circle maps with periodic points the set of all periodic points is dense in S 1 . Moreover, Blokh in [20] showed that transitive circle maps with periodic points have positive topological entropy.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Coven and Mulvey in [23] extended Theorem 1.1 to the circle proving that for transitive circle maps with periodic points the set of all periodic points is dense in S 1 . Moreover, Blokh in [20] showed that transitive circle maps with periodic points have positive topological entropy.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…We now refer the reader to the third paragraph of the proof of Theorem A of [2]. That paragraph, with some cosmetic changes, completes the proof of the present lemma.…”
Section: Preliminary Lemmasmentioning
confidence: 81%
“…This result fails for maps of the circle, as we show in an example. The notion of a one-way interval for a map of the circle is introduced in [2] where dynamic properties of circle maps are explored. In the present paper, we continue the study of one-way intervals for maps of the circle.…”
Section: Introductionmentioning
confidence: 99%
“…Define x, arbitrarily for 2"(j2)< r < P"(Jl). For i >Jl the term p"(i) is the highest subscript occurring in (2), while for i< J2 the term 2"(0 is the lowest subscript occurring in (2). Therefore the system can be solved consistently, showing that I -0" is surjective.…”
Section: Jek(ni)mentioning
confidence: 94%
“…Note that if 2 is a character then U"(2) = 20" = 0n (2). Let f~ = ~ cij2~, where j=O 4o = la, the cijsC, and the 2f~G.…”
Section: The Endomorphism Theoremmentioning
confidence: 99%